ANALISIS HUBUNGAN KOMPETENSI PRODUKSI FILM DENGAN MINAT BERWIRAUSAHA MAHASISWA - Endah Wulandari (JURNAL ILMIAH EDUNOMIKA, 2025)
The rapid growth of the creative industry has increased the demand for graduates who possess not only technical expertise but also entrepreneurial competencies. This study aims to examine the relationship between film production competence and entrepreneurial intention among undergraduate students in the Film and Television Study Program. A quantitative research approach was employed using a survey method. Data were collected through a structured questionnaire distributed to active students selected using purposive sampling. The research instrument measured film production competence, including pre-production, production, and post-production skills, as well as students' entrepreneurial intention. The collected data were analyzed using the Statistical Package for the Social Sciences (SPSS), including descriptive statistics, validity and reliability tests, normality testing, Pearson correlation analysis, and simple linear regression. The findings are expected to provide empirical evidence regarding the contribution of film production competence to students' entrepreneurial intention. The study is anticipated to offer valuable insights for higher education institutions in developing entrepreneurship-oriented curricula that integrate creative industry competencies, thereby enhancing graduates' readiness to establish sustainable businesses in the film and audiovisual sectors.